MINUMAN BERALKOHOL DAN SOPIR ANGKUTAN KOTA (PETE-PETE) DI KOTA KENDARI - Nisar Aris Rina; Akhmad Marhadi (KABANTI : Jurnal Kerabat Antropologi, 2023)
This research aims to find out the reasons why this city transportation driver consumes alcohol, to find out and describe how the transportation driver gets alcohol and what types of drinks they consume to analyze the data in this study using Jean Paul Sarte's Phenomenology theory. The data collection techniques used in this study are informant determination techniques, data collection techniques, involved observation, ethnographic interviews and data analysis techniques. This research is a study using ethnographic research methods. The results of this study indicate that one of the factors causing them to consume alcohol is due to a sense of trial and error so that they become addicted and also due to life problems. The way they get alcohol is by asking friends, taxing and buying their own drinks. As for the types of drinks they usually consume, usually traditional alcoholic drinks such as arak, kameko, pongasi and ballo because traditional alcoholic drinks are very easy to find and the price is also very affordable compared to alcoholic drinks that already have a brand or brand.